Conexões sociopolíticas, planejamento tributário e elisão fiscal: evidências no Brasil - Holanda, Allan Pinheiro (2022)
It is argued that tax avoidance in Brazil does not occur solely through the accounting movement in the calculation of taxes owed by the firm, but also by acting of managers and business interest groups in establishing connections with the political class and relevant social decision-making groups. It is questioned whether the level of tax burden results exclusively from internal actions in the calculation of taxes or it is complementary to the socio-political action of the firm. The objective was established to investigate the effect of sociopolitical connections of Brazilian firms on tax planning mechanisms, tax burden and owner profitability. The thesis is applied to the investigation that in Brazil, firms implement tax planning actions, through institutional connections with socio-political and decision-making groups, producing effects at the level of the tax burden and owner profitability. The research establishes as a theoretical basis the concept that regulation is an economic good, capable of being negotiated between suppliers, regulators and the political class, and demanders, business interest groups. It starts from the idea that the regulatory system is shaped to ensure the maximization of the utility function of demanders and suppliers as expressed in Stigler's theory of economic regulation (1971). Applying a functionalist approach and based on the theoretical reasoning raised, a theoretical model was developed that relates sociopolitical connections, tax planning processes, tax avoidance and owner profitability, which is tested using univariate analysis techniques - mean difference test (parametric and non-parametric), correlation analysis (also parametric and non-parametric) and correspondence analysis - with the aim of showing relationships between the groups of variables used and multivariate techniques - multiple linear regression, with estimation via the Generalized Method of Moments - System (GMM- SYS), and structural equation modeling - with the aim of investigating the relationship of dependence, meaning and significance between the research variables. A sample of 209 companies listed on B3 was used, totaling 1,125 company-years, with data available between the years 2011 and 2018. The findings lead us to accept the proposed thesis. It can be inferred that there is a significant association between political and regulatory classes and business groups. Tax aggressiveness is driven by sociopolitical connections and effectively leads to a lower tax burden for the firms that apply it. There is still a strong differentiation in the tax burden according to the firm's sector of, without having identified the origin of such explanation in the accounting data, it can be speculated, for future studies, that it is in the editing of subsidies, grants and exemptions that are given ex-ante to x accounting record. No evidence was found that tax avoidance is related to owner profitability. It is worth that the designed theoretical model did not meet the econometric adjustments necessary for the structural equation modeling, therefore, not producing a comprehensive model of the relationships studied. Finally, for future studies, the possible influence of sociopolitical connections is not an exclusive practice of the tax process, as other researches, associated with fiscal expenditures and financing in official banks can be studied. Information on lobbying, the essence of the subject investigated, is non-existent in Brazil, which led to the use substitutes for the definition of sociopolitical connections.